Hunger and food trough a historic perspective - Stronzake, Janaína (Revista Española de Desarrollo y Cooperación, 2023)
This article discusses the transformation of the condition of food, which has gone from being a right to becoming a commodity as part of the process of the formation and expansion of capitalism. The results of this process are thousands of hungry people, and a few increasingly enriched transnational companies.